Effects of motor intervention in elderly patients with dementia: An analysis of randomized controlled trials - Christofoletti, Gustavo [UNESP]; Oliani, Merlyn Mércia [UNESP]; Gobbi, Sebastiao [UNESP]; Stella, Florindo [UNESP] (Wolters Kluwer, 2007)
The objective of this study was to analyze randomized controlled trials published in the last decades involving motor intervention as a treatment for dementia, based on Physiotherapy Evidence Database (PEDro) criteria. A database search was performed using the following keywords: randomized controlled trial, dementia, physiotherapy, physical therapy, occupational therapy, physical education, motor approach, exercise, and physical activity. Ten trials were found: 4 related to physiotherapy, 3 to occupational therapy, 1 to physical education, and 2 to interdisciplinary motor intervention. The efficacy of motor intervention was confirmed in the following variables: psychosocial function, physical health and function, affective status, and caregiver's distress (P < .05). Results related to mobility were not significant (P > .05). Behavior, cognitive performance, activities of daily living, and risk of falls were not similar among the articles. From a total score of 10 points, with excellence characterized as the highest punctuation, the articles were classified between 3 and 7 by PEDro. Motor intervention was shown to be an alternative for minimizing physical and mental decline. PEDro has been confirmed as a very reliable tool to analyze studies and as an evaluation criteria, both qualitative and quantitative, allowing the establishment of motor intervention strategies for the treatment of patients with dementia. © 2007 Lippincott Williams & Wilkins, Inc.
Keywords: Dementia; Motor intervention; Randomized controlled trials; affect; aged; behavior; caregiver; clinical trial; cognition; controlled clinical trial; controlled study; daily life activity; data base; dementia; distress syndrome; elderly care; exercise; falling; female; health; human; major clinical study; male; occupational therapy; patient mobility; physical activity; physical education; physiotherapy; qualitative analysis; quantitative analysis; randomized controlled trial; reliability; risk assessment; social psychology